Bronchial carcinoid tumor with vascular supply from thoracic aorta - BAYRAM, MEHMET; Döngel, Isa; IMAMOGLU, Hakan; Bayram, MEHMET (My University, 2013)
Bronchial carcinoid tumors are neuroendocrine tumors which account for approximately 1% of tracheobronchial tree tumors. Symptoms depend on localization and size of tumor or secreting neuroendocrine hormones. In this article, we report a 48-year-old female case who was admitted with dyspnea, retrosternal pain and asthma-like symptoms. Computed tomography revealed a centrally located mass lesion with vascular supply from an aberrant artery arising from the thoracic aorta. No endobronchial lesion was present on bronchoscopy. Left thoracotomy was performed and aberrant artery was ligated and cut. Left lower lobectomy and mediastinal lymph node dissection were performed. Histopathological examination revealed a typical carcinoid tumor without lymph node invasion. After a 21-month follow-up, she is clinically well without recurrence.